The distinction between symptoms and traits in the Hierarchical Taxonomy of Psychopathology (HiTOP) - DeYoung, Colin G.; Chmielewski, Michael; Clark, Lee Anna; Condon, David M.; Kotov, Roman; Krueger, Robert F.; Lynam, Donald R.; Markon, Kristian E.; Miller, Joshua D.; Mullins‐Sweatt, Stephanie N.; Samuel, Douglas B.; Sellbom, Martin; et al. (Journal of personality, 2022)
The Hierarchical Taxonomy of Psychopathology (HiTOP) is an empirically and quantitatively derived dimensional classification system designed to describe the features of psychopathology and, ultimately, to replace categorical nosologies. Among the constructs that HiTOP organizes are “symptom components” and “maladaptive traits,” but past HiTOP publications have not fully explicated the distinction between symptoms and traits. We propose working definitions of symptoms and traits and explore challenges, exceptions, and remaining questions. Specifically, we propose that the only systematic difference between symptoms and traits in HiTOP is one of time frame. Maladaptive traits are dispositional constructs that describe persistent tendencies to manifest features of psychopathology, whereas symptoms are features of psychopathology as they are manifest during any specific time period (from moments to days to months). This has the consequence that almost every HiTOP dimension, at any level of the hierarchy, can be assessed as either a trait or a symptom dimension, by adjusting the framing of the assessment. We discuss the implications of these definitions for causal models of the relations between symptoms and traits and for distinctions between psychopathology, normal personality variation, and dysfunction.